The effects of resistance training on muscular fitness, muscle morphology, and body composition in elite female athletes: a systematic review - Zouita, A.; Darragi, M.; Bousselmi, M.; Sghaeir, Z.; Clark, C. C. T.; Hackney, A. C.; Granacher, U.; Zouhal, H. (Sports Medicine, 2023)
Background: Well programmed strength and conditioning training is an indispensable part of the long-term training process for athletes in individual and team sports to improve performance and prevent injuries. Yet, there is a limited number of studies available that examine the effects of resistance training (RT) on muscular fitness and physiological adaptations in elite female athletes. Objectives: This systematic review aimed to summarize recent evidence on the long-term effects of RT or combinations of RT with other strength-dominated exercise types on muscular fitness, muscle morphology, and body composition in female elite athletes. Materials and Methods: A systematic literature search was conducted in nine electronic databases (Academic Search Elite, CINAHL, ERIC, Open Access Theses and Dissertations, Open Dissertations, PsycINFO, PubMed/MEDLINE, Scopus, and SPORTDiscus) from inception until March 2022. Key search terms from the MeSH database such as RT and strength training were included and combined using the operators "AND," "OR," and "NOT". The search syntax initially identified 181 records. After screening for titles, abstracts, and full texts, 33 studies remained that examined the long-term effects of RT or combinations of RT with other strength-dominated exercise types on muscular fitness, muscle morphology, and body composition in female elite athletes. Results: Twenty-four studies used single-mode RT or plyometric training and nine studies investigated the effects of combined training programs such as resistance with plyometric or agility training, resistance and speed training, and resistance and power training. The training duration lasted at least 4 weeks, but most studies used ~ 12 weeks. Studies were generally classified as `high-quality` with a mean PEDro score of 6.8 (median 7). Irrespective of the type or combination of RT with other strength-dominated exercise regimens (type of exercise, exercise duration, or intensity), 24 out of 33 studies reported increases in muscle power (e.g., maximal and mean power; effect size [ES]: 0.23 < Cohen`s d < 1.83, small to large), strength (e.g., one-repetition-maximum [1RM]; ES: 0.15 < d < 6.80, small to very large), speed (e.g., sprint times; ES: 0.01 < d < 1.26, small to large), and jump performance (e.g., countermovement/squat jump; ES: 0.02 < d < 1.04, small to large). The nine studies that examined the effects of combined training showed significant increases on maximal strength (ES: 0.08 < d < 2.41, small to very large), muscle power (ES: 0.08 < d < 2.41, small to very large), jump and sprint performance (ES: 0.08 < d < 2.41, small to very large). Four out of six studies observed no changes in body mass or percentage of body fat after resistance or plyometric training or combined training (ES: 0.026 < d < 0.492, small to medium). Five out of six studies observed significant changes in muscle morphology (e.g., muscle thickness, muscle fiber cross-sectional area; ES: 0.23 < d < 3.21, small to very large). However, one study did not find any changes in muscle morphology (i.e., muscle thickness, pennation angle; ES: 0.1 < d < 0.19, small). Conclusion: Findings from this systematic review suggest that RT or combined RT with other strength-dominated exercise types leads to significant increases in measures of muscle power, strength, speed, and jump performance in elite female athletes. However, the optimal dosage of programming parameters such as training intensity and duration necessary to induce large effects in measures of muscular fitness and their physiological adaptations remain to be resolved in female elite athletes.